(untitled) (Fiep Bulletin - online, 2014)
The acute diseases of the respiratory system are the main reasons of maintenance of the high mortality rates among children in their first five years of life. Among the risk factors, the environmental conditions can be evidenced (seasons, people gatherings, atmospheric pollution, domestic pollution and tobacco use), witch play an important role in the causal chain of those diseases. The Child’s and Adolescent’s Statute reaffirms the "duty of the family, of the society and of the State in assuring the child and the adolescent, with absolute priority, the right to the life, to health, to feeding, to education, to leisure, to get a profession, to culture, to dignity, to respect, to freedom and the family and community coexistence, besides putting them safe of every negligence way, discrimination, exploration, violence, cruelty and oppression". This is a descriptive research of the survey type, and had the purpose of verifying the existence of poor children with respiratory problems and the need of a respiratory Physiotherapy service. Evaluations were performed in Health Units of the South and East Districts of the city of Natal in the state of Rio Grande do Norte. There are approximately 1120 children receiving medical assistance per month, with an average of 224 children a week. The pathologies with the largest incidence were the pneumonias and the IRAS, and in 80% of the health units physiotherapy services do not exist. The majority of the interviewees reinforced the idea that it is necessary to have a preventive service with a physiotherapist in the health team in the units of community service. There was a need of implementing a respiratory physiotherapy program for children with acute and chronic respiratory problems, because 90% of the interviewees reaffirmed the importance of this kind of program for the community.